Nitric Oxide Induces Autophagy in Triticum aestivum Roots - Farida Minibayeva; Anastasia Mazina; Natalia Gazizova; Svetlana Dmitrieva; Anastasia Ponomareva; Daniya Rakhmatullina (MDPI AG, 2023)
Autophagy is a highly conserved process that degrades damaged macromolecules and organelles. Unlike animals, only scant information is available regarding nitric oxide (NO)-induced autophagy in plants. Such lack of information prompted us to study the roles of the NO donors' nitrate, nitrite, and sodium nitroprusside in this catabolic process in wheat roots. Furthermore, spermine, a polyamine that is found in all eukaryotic cells, was also tested as a physiological NO donor. Here, we show that in wheat roots, NO donors and spermine can trigger autophagy, with NO and reactive oxygen species (ROS) playing signaling roles based on the visualization of autophagosomes, analyses of the levels of NO, ROS, mitochondrial activity, and the expression of autophagic (ATG) genes. Treatment with nitrite and nitroprusside causes an energy deficit, a typical prerequisite of autophagy, which is indicated by a fall in mitochondrial potential, and the activity of mitochondrial complexes. On the contrary, spermine sustains energy metabolism by upregulating the activity of appropriate genes, including those that encode glyceraldehyde 3-phosphate dehydrogenase GAPDH and SNF1-related protein kinase 1 SnRK1. Taken together, our data suggest that one of the key roles for NO in plants may be to trigger autophagy via diverse mechanisms, thus facilitating the removal of oxidized and damaged cellular constituencies.